MARKETING COMMUNICATION STRATEGY IMPLEMENTATION OF NOVEL “REIVAN AND REINA” BY CHRISTA BELLA IN INTERNET COMMUNITY FORUM - Supriyanto Supriyanto (Metakom, 2019)
This study aims to determine the process of marketing communication strategy novel "Reivan & Reina" by Christa Bella in Internet Community Forum this studyconducted on Facebook Internet Media. This research uses descriptive method by using qualitative approach. Based on the results of this study obtained the results of marketing communication strategy conducted by novelist Christa Bella in his work "Reivan & Reina" is very interesting because it has many reviews discussed about the strategies undertaken especially in the world of story writing. The presence of Internet Community Forum Facebook is a form of technological advances in the field of communication media so that it can be easily understood and interesting to be reviewed and create new business opportunities. Keywords : Internet community forum, Strategy communication, Marketing mix, Purchasing decisions.